Embolization of left atrial appendage closure devices: A systematic review of cases reported with the watchman device and the amplatzer cardiac plug. Issue 1 (25th February 2015) - Aminian, Adel; Lalmand, Jacques; Tzikas, Apostolos; Budts, Werner; Benit, Edouard; Kefer, Joelle
<x xml:space="preserve">Abstract</x> Objectives We sought to provide a systematic review of reported cases of LAA closure device embolization by focusing on the two most commonly implanted devices: the Watchman (WM) device and the Amplatzer Cardiac Plug (ACP). Methods A comprehensive search of the Pubmed database was conducted until October 1, 2014. Studies were included if they described at least 1 case of embolization of the WM and/or the ACP. Results A total of 20 studies reporting 31 cases of device embolization were identified, including 13 cases with WM and 18 cases. The timing of embolization was described in 29 cases and was categorized as acute in 20 cases (65%) and late in 9 cases (30%). The anatomical location of embolized devices was reported in 21 cases: into the aorta in 9 cases, into the left ventricle (LV) in 9 cases and into the left atrial cavity in 3 cases. As compared to embolization into the aorta or the left atrial cavity, device embolization into the LV was associated with a higher rate of surgical retrieval (8/9 vs 2/12; 88% vs 17%, P = 0.0019). Major adverse events related to device embolization occurred in three patients (9.6%). Conclusions LAA closure device embolization occurs mainly in the periprocedural period but late embolizations are not uncommon. Although embolization into the aorta or the left atrium can be successfully managed by percutaneous techniques in most cases, device embolization into the LV is associated with a higher rate of surgical retrieval, increasing thereby procedure‐related morbidity. © 2015 Wiley Periodicals, Inc.